The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/bjd.16049
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychological comorbidity in people with vitiligo: a systematic review and meta-analysis

Abstract: A range of psychological outcomes are common in people with vitiligo. The prevalence of anxiety was influenced by type of screening tool, suggesting the need for validation of psychological outcome screening tools in the field of dermatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 46 publications
(57 reference statements)
2
77
3
3
Order By: Relevance
“…An uncontrolled study of Indian adults and children found that vitiligo patients with suicidal ideation were more likely to turn to alcohol as a coping mechanism . A recent systematic review of 29 studies showed that other MH comorbidities for example adjustment disorder, substance disorder and alcohol abuse were evident in vitiligo patients . The present study found that vitiligo was associated with primary hospitalization for virtually every MH disorder examined and was more likely to be hospitalized for suicidal risk, alcohol and substance abuse.…”
Section: Discussionsupporting
confidence: 61%
“…An uncontrolled study of Indian adults and children found that vitiligo patients with suicidal ideation were more likely to turn to alcohol as a coping mechanism . A recent systematic review of 29 studies showed that other MH comorbidities for example adjustment disorder, substance disorder and alcohol abuse were evident in vitiligo patients . The present study found that vitiligo was associated with primary hospitalization for virtually every MH disorder examined and was more likely to be hospitalized for suicidal risk, alcohol and substance abuse.…”
Section: Discussionsupporting
confidence: 61%
“…The clinical evaluation was done by independent dermatologists. The reaction to repigmentation therapy was based on the evaluation of doctors: excellent for 75%‐100% repigmentation, good for 50%‐75%, moderate for 25%‐50%, and mild for <25% …”
Section: Methodsmentioning
confidence: 99%
“…Quantitative reaction assessment was also conducted for accurate statistical assessment in a numerical proportion …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin diseases can have considerable impact on a patient's well‐being and can evoke negative emotions such as shame, embarrassment, and stress. They can also make patients feel inferior, stigmatized, and discriminated against, particularly, if the disease develops on exposed areas of the body 7 . Vitiligo is one such disease, and it is reported that roughly 75% of vitiligo patients have a psychological disorder 3 .…”
Section: Psychodermatologymentioning
confidence: 99%